Violence and Lasciviousness: Representations of African and Asian Women and Men in French Erotic Illustrations, Early to Mid-20th Century - (:unkn) unknown (My University, 2018)
During the first half of the 20th century, notions of geographical otherness were frequent inspirations for French erotic literature and illustrations. In this context, Africans and Asians became favorite subjects for writers and artists. This study explores the ways in which Africans and Asians were represented by western illustrators to determine whether western artists maintained established constructions or created new ones. While the context of the first half of the 20th century gave rise to new motifs in erotic illustration, the classic diptych between violence and voluptuousness continued to frame most representations of Africans and Asians.
Keywords: African Research